Laboratory technique for evaluation of methods of suppressing nuisance dust - S. P. Sharples; S. P. Godby (The Institute of Materials, Minerals and Mining, 1905)
Wind-tunnel tests were carried out of the conditions under which nuisance dust particles (100-1 000 micrometres) become entrained by wind. A laser entrainment monitoring system (LEMS) was used, and was found to provide an accurate means of assessing nuisance dust emissions from a surface. Accurate determination of the threshold entrainment velocity of dusts using the LEMS gives a baseline against which the performance of dust control techniques can be evaluated. Minerals tested included coal, petroleum coke, limestone, sand and pulverised fuel ash. Pilot field trials of a portable wind tunnel equipped with the LEMS have been successfully completed, providing a means of validating laboratory results in the field